PENGARUH AKUNTABILITAS, TRANSPARANSI DAN PARTISIPASI MASYARAKAT TERHADAP EFEKTIVITAS PENGELOLAAN ALOKASI DANA DESA DI DESA PURWOREJO KECAMATAN KOTA GAJAH KABUPATEN LAMPUNG TENGAH - Ridwan Indra Hermawan; Yulita Zanaria; Nedi Hendri (Jurnal Akuntansi AKTIVA, 2021)
This study aimed to determine the effect of accountability, transparency, and community participation on the effectiveness of managing the allocation of funds in Purworejo village, Kotagajah Sub-district, Lampung Tengah district. Data were obtained from the results of written data and questionnaires to 97 respondents who were taken using the formula from Slovin. The data analysis of this research was carried out using analysis of instrument testing, classical assumptions and hypotheses. The results of this study indicated that the variables of accountability, transparency and community participation in the management of village funds had a positive and significant effect on the effectiveness of the management of village fund allocations in Purworejo Village, Kotagajah Sub-district, Central Lampung district.